Inherent and apparent optical properties in coastal waters: a study of the Clyde Sea in early summer - McKee, D; Cunningham, A; Slater, J; Jones, K.J; Griffiths, C.R (Estuarine, coastal and shelf science, 2003)
Profiles of absorption and attenuation coefficients, downward irradiance and upward radiance were measured at 14 stations in the Clyde Sea during May 2000. The absorption coefficient at 676 nm was linearly correlated with chlorophyll concentration ( R 2=0.88), and the ratio of scattering to absorption in this waveband could be used to discriminate between phytoplankton and other suspended material. The radiance and irradiance measurements showed rapid attenuation of blue and red wavelengths near the surface, while the red component was augmented by chlorophyll fluorescence in deeper waters. Throughout the Clyde Sea the relationship between absorption coefficients a( λ), scattering coefficients b( λ), and diffuse attenuation coefficients for downward irradiance K d( λ) was well described by a function proposed by Kirk (Limnol. Oceanogr. 29 (1984) 350). A procedure was devised for retrieving inherent optical properties from measurements of the radiance reflectance and diffuse attenuation coefficient that was able to successfully predict measured absorption coefficients throughout the study area ( R 2=0.95). Backscattering ratios estimated using this procedure varied with depth and location according to changes in the relative concentration of phytoplankton to other particles. Tables of measured inherent and apparent optical properties and derived backscattering ratios for near-surface water are provided for modelling radiative transfer in the Clyde Sea and other coastal areas subject to freshwater influence.